Monitoring the Wet-Heat Inactivation Dynamics of Single Spores of Bacillus Species by Using Raman Tweezers, Differential Interference Contrast Microscopy, and Nucleic Acid Dye Fluorescence Microscopy - Zhang, Pengfei (American Society for Microbiology, 2011)

(untitled)
Dynamic processes during wet-heat treatment of individual spores of Bacillus cereus, Bacillus megaterium, and Bacillus subtilis at 80 to 90°C were investigated using dual-trap Raman spectroscopy, differential interference contrast (DIC) microscopy, and nucleic acid stain (SYTO 16) fluorescence microscopy. During spore wet-heat treatment, while the spores' 1:1 chelate of Ca(2+) with dipicolinic acid (CaDPA) was released rapidly at a highly variable time T(lag), the levels of spore nucleic acids remained nearly unchanged, and the T(lag) times for individual spores from the same preparation were increased somewhat as spore levels of CaDPA increased. The brightness of the spores' DIC image decreased by ∼50% in parallel with CaDPA release, and there was no spore cortex hydrolysis observed. The lateral diameters of the spores' DIC image and SYTO 16 fluorescence image also decreased in parallel with CaDPA release. The SYTO 16 fluorescence intensity began to increase during wet-heat treatment at a time before T(lag) and reached maximum at a time slightly later than T(release). However, the fluorescence intensities of wet-heat-inactivated spores were ∼15-fold lower than those of nutrient-germinated spores, and this low SYTO 16 fluorescence intensity may be due in part to the low permeability of the dormant spores' inner membranes to SYTO 16 and in part to nucleic acid denaturation during the wet-heat treatment.